PROFILE OF PROBLEM SOLVING ABILITY IN COMPLETING FRACTION QUESTION OF CLASS V STUDENTS VIEWED FROM LEARNING STYLES - Febriani, Ari Ana; Muslim, Rachmat Imam; Aditama, Madya Giri (Prosiding University Research Colloquium, 2023)
The purpose of this study was to determine the profile of problem-solving abilities in grade 5 students’ fractions in terms of learning styles. The research was conducted at SD Muhammadiyah Limpung with a total of 27 students. The research method used is descriptive qualitative method. Data collection techniques in this study used questionnaires, tests and interviews. For the validity or validity of the data using the triangulation method. The results of the study are: 1) students with a visual learning style have fulfilled all indicators of problem solving ability 2) Students with an auditory learning style have fulfilled the indicators of understanding the problem, preparing a problem solving plan and carrying out the problem solving plan but in the stage of re- examining students with an auditory learning style felt incapable of doing so. 3) Students with a kinesthetic learning style have fulfilled 2 indicators, namely understanding the problem and implementing a problem-solving plan while for the other 2 indicators students are deemed incapable of doing so. In this study it was also found that kinesthetic students experienced pseudo-thoughts where the child answered correctly but did not understand the concept; students only imitated the examples given by the teacher.